THE EFFICIENCY OF IMPLEMENTING A PROPOSED PROGRAM CENTERED ON THE CEREBRAL HEMISPHERES TO FOSTER FUTURE THINKING AND ENHANCE COMPREHENSION OF HISTORICAL EVENTS AMONG FOURTH GRADE LITERARY STUDENTS - Mona Hasanee Mohamed (American Journals Publishing, 2024)
The study’s goal is to develop an educational program based on the cerebral hemispheres and assess how well fourth grade literary students’ future cognitive abilities and understanding of historical events would fare. (The researcher em-ployed an experimental approach and a quasi-experimental design with a post-test for two equal groups in order to accomplish the goals of the study. The re-searcher intentionally selected sixty-four fourth-grade literary students and split the research sample into two groups: an experimental group, which received the suggested educational program, and a control group, which underwent conven-tional research with 32 students. The two study groups were compared in terms of the factors intelligence, future thinking skills scale, and chronological age). Based on the cerebral hemispheres, a learning program was developed to stimu-late the combined functioning of the two hemispheres of the mind. In addition, two research tools were developed, including (20 items) historical events test that assessed future thinking skills. The coefficients and content validity of the two tests were confirmed. In addition to differentiation and difficulty, the Cronbach alpha equation was utilized to determine the test's reliability. The sec-ond tool is a 35-item future thinking scale. Additionally, its psychometric prop-erties were validated. Presenting the concept to a panel of arbitrators and experts in the educational and psychological sciences, as well as social studies and histo-ry education, confirmed its validity. The experiment was executed in the first semester of the academic year 2023–2024. The two study groups were instruct-ed by the researcher, with the control group using the standard procedure and the experimental group using the educational program based on the cerebral hemispheres. Each study group took the historical events exam and the future thinking scale. Data was gathered and then statistically examined using the fol-lowing suitable statistical techniques in order to evaluate the validity of the hy-potheses: T-test for two independent and non-independent samples, Alpha-Cronbach equation, Pearson correlation coefficient, Gamma correlation coeffi-cient. The study findings showed that the suggested educational program out-performed the conventional approach in enhancing fourth grade liter-ary students’ comprehension of historical events and their degree of future thinking. Several conclusions were made in view of the study findings, the most significant of which is the use of the cerebral hemispheres hypothesis in social studies and history instruction at all academic levels.
Keywords: Effectiveness - the theory of the cerebral hemispheres - historical events - com-prehension - future thinking